Water-Soluble and Insoluble Polymers and Biopolymers for Biomedical, Environmental, and Biological Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The use of polymers in biological applications is defined by the interactions promoted between living organisms and polymeric chains, which are generally associated with the polymers’ hydrophilic and hydrophobic behaviors. However, these water-friendly structures are also very useful for other applications, such as the adsorption of pollutants from sewage water. The modulation of the final properties of water-soluble and insoluble polymers tends to define the spectra of features associated with their final applications.